Genetically modified food and consumer risk responsibility: The effect of regulatory design and risk type on cognitive information processing. - Ashkan Pakseresht (Public Library of Science (PLoS), 2021)
The use of agro-biotechnology has raised consumer concerns about environmental, health, socio-economic and ethical risks. This study examines how regulatory policies regarding genetically modified (GM) food production affect consumers' cognitive information processing, in terms of perceived risk, self-control, and risk responsibility. There is further analysis of whether the effect of policy design is moderated by risk type. Data was generated in a field experiment (n = 547), including four different policy scenario treatments (banned, research and development, import, and full commercialization). The results reveal that policy scenarios where GM food is available on the market are associated with higher levels of perceived risk and lower levels of self-control compared with policies where GM food is banned. There was no evidence of policy scenarios affecting consumer willingness to assign personal risk responsibility. However, among participants who indicated health risks as their main concern, there was an effect from the policy scenario on self-risk responsibility as mediated through perceived risk and self-control. The results suggest that health-conscious consumers tend to attribute less responsibility to themselves in situations where a genetically modified product was commercialized. These findings indicate a need to clarify guideline recommendations for health-related risks associated with foods derived from biotechnology.